2019
DOI: 10.3389/fneur.2019.00702
|View full text |Cite
|
Sign up to set email alerts
|

Functional Translocation of Broca's Area in a Low-Grade Left Frontal Glioma: Graph Theory Reveals the Novel, Adaptive Network Connectivity

Abstract: We describe frontal language reorganization in a 50–60 year-old right-handed patient with a low-grade left frontotemporal insular glioma. Pre-operative fMRI revealed robust activation in the left superior temporal gyrus (Wernicke Area, WA) and in the right inferior frontal gyrus (right anatomical homolog of Broca Area, BA). Intra-operative cortical stimulation of the left inferior frontal gyrus and adjacent cortices elicited no speech deficits, and gross total resection including the expected location of BA re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 30 publications
2
25
0
Order By: Relevance
“…With regard to the language network, compensatory recruitment of perilesional areas was observed following tumor invasion of crucial areas including Broca’s area (e.g., Benzagmout et al, 2007 , Lubrano et al, 2010 , Thiel et al, 2001 ; for single cases, see Chan et al, 2019 , De Benedictis et al, 2012 , Meyer et al, 2003a , Plaza et al, 2009 ), perisylvian regions such as Wernicke’s area ( Ille et al, 2019 ; Thiel et al, 2001 ), and the left insula (e.g., Duffau et al, 2006 ; for single cases, see Duffau et al, 2001 , Li et al, 2019 ). A limited but feasible perilesional compensatory activation was also observed for the premotor cortex, which also supports language functions (e.g., Gil Robles et al, 2008 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…With regard to the language network, compensatory recruitment of perilesional areas was observed following tumor invasion of crucial areas including Broca’s area (e.g., Benzagmout et al, 2007 , Lubrano et al, 2010 , Thiel et al, 2001 ; for single cases, see Chan et al, 2019 , De Benedictis et al, 2012 , Meyer et al, 2003a , Plaza et al, 2009 ), perisylvian regions such as Wernicke’s area ( Ille et al, 2019 ; Thiel et al, 2001 ), and the left insula (e.g., Duffau et al, 2006 ; for single cases, see Duffau et al, 2001 , Li et al, 2019 ). A limited but feasible perilesional compensatory activation was also observed for the premotor cortex, which also supports language functions (e.g., Gil Robles et al, 2008 ).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, several single-case studies reported preoperative translocation of either Broca’s (e.g., Holodny et al, 2002 , Li et al, 2019 ) or Wernicke’s area (e.g., Petrovich et al, 2004 ), even though the other non-affected area was still active in the left (language-dominant) hemisphere. Notably, this reorganization then enabled total resection of the no-longer functional left area, without causing permanent language deficits.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The high incidence of postoperative cognitive decline in patients with low grade glioma could be explained by some functional activity remaining within the tumour mass. 18 Focal brain tumours produce global changes in the functionally complex and networked brain architecture, which may aid in our understanding of patients' larger scale Intraoperative neurophysiological monitoring refers to a group of procedures used to monitor neural pathways during high risk operations to help surgeons avoid damage to the nervous system. It includes techniques to identify impending damage and techniques to map the vital structures of the nervous system Awake brain surgery (awake craniotomy) is a neurosurgical technique that allows a surgeon to remove the tumour or epileptic tissue while the patient is awake to avoid brain damage.…”
Section: Challenges In Brain Healthmentioning
confidence: 99%
“…The high incidence of postoperative cognitive decline in patients with low grade glioma could be explained by some functional activity remaining within the tumour mass. 18 Focal brain tumours produce global changes in the functionally complex and networked brain architecture, which may aid in our understanding of patients’ larger scale neurological manifestations and provide a framework for improving plasticity. 19 Of note, recent reports have linked neuronal excitability with growth of gliomas and brain metastases.…”
Section: Challenges In Brain Healthmentioning
confidence: 99%